Institutional Distance and Headquarters-Subsidiary Relationship Quality: The Moderating Role of Institutionalization of Headquarters’ Practices in Subsidiaries - Li, Forest; Jiang, Fuming (2016)
Through the lens of the institutional theory, we developed and empirically tested a contingency theoretical framework that examines the effects of formal and informal institutional distances on the quality of the headquarters–subsidiary relationship, and how such effects are contextualized by internal institutionalization of headquarters’ practices in subsidiaries of Chinese multinational enterprises (MNEs). Data were collected from both the headquarters of 297 Chinese MNEs and their respective subsidiaries. The results show that regulative and cultural distances are positively associated with the quality of the headquarters–subsidiary relationship, and that these positive relationships are stronger when subsidiaries institutionalize headquarters’ practices to a higher degree. Theoretical and practical implications are highlighted in the paper.